2009
DOI: 10.1254/jphs.08287fp
|View full text |Cite
|
Sign up to set email alerts
|

Etodolac Attenuates Mechanical Allodynia in a Mouse Model of Neuropathic Pain

Abstract: Abstract. Cyclooxygenase (COX) contributes to neuropathic pain after peripheral nerve injury, yet COX inhibitors are generally ineffective against mechanical allodynia and hyperalgesia in neuropathic pain patients and animal models. In the present study, we investigated the effects of etodolac, a selective COX-2 inhibitor, on mechanical allodynia in mice after partial sciatic nerve ligation (PSNL) compared to indomethacin (a nonselective COX inhibitor) or celecoxib (a selective COX-2 inhibitor). PSNL decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 22 publications
1
16
1
Order By: Relevance
“…15) We have previously reported that etodolac, but not indomethacin or celecoxib, attenuates allodynia in PSNL mice. 13) In the present study, neither diclofenac nor meloxicam showed anti-allodynic effects in the PSNL model. Taken together, these results suggest that the anti-allodynic mechanism of etodolac is not mediated by COX-2 inhibition.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…15) We have previously reported that etodolac, but not indomethacin or celecoxib, attenuates allodynia in PSNL mice. 13) In the present study, neither diclofenac nor meloxicam showed anti-allodynic effects in the PSNL model. Taken together, these results suggest that the anti-allodynic mechanism of etodolac is not mediated by COX-2 inhibition.…”
Section: Discussioncontrasting
confidence: 67%
“…12) We recently reported that etodolac attenuates allodynia in a mouse model of neuropathic pain. 13) The mechanism of the anti-allodynic effects of etodolac has not yet been established, but COX inhibition is unlikely to be involved because the COX inhibitors indomethacin and celecoxib do not attenuate the allodynia. There is still a question which enantiomer of etodolac produces the anti-allodynic effect in mice.…”
mentioning
confidence: 99%
“…55) However, NSAIDs are reported to be ineffective against neuropathic pain, including CPSP in basic or clinical study. 14,56,57) Indomethacin, an NSAID, had no effect on the paw withdrawal threshold throughout the assessment period.…”
Section: )mentioning
confidence: 99%
“…14,56,57) Indomethacin, an NSAID, had no effect on the paw withdrawal threshold throughout the assessment period. 55) Additionally, another NSAID, diclofenac, had no effect on oxaliplatin-induced cold hypersensitivity. 14) In the present study, we also found that administration of the NSAID indomethacin had no effect on the BCAO-induced mechanical allodynia, suggesting that NSAIDs are not useful in CPSP treatment.…”
Section: )mentioning
confidence: 99%
“…It is caused by damage to the nervous system and is characterized by spontaneous pain, hyperalgesia and allodynia [1]. We have previously reported that etodolac, a nonsteroidal anti-inflammatory drug (NSAID) and selective cyclooxygenase-2 (COX-2) inhibitor, attenuates allodynia in a mouse model of neuropathic pain [2]. The mechanism of the antiallodynic effect of etodolac has not yet been established, but COX inhibition is unlikely to be involved because other COX inhibitors do not attenuate the allodynia [2,3].…”
Section: Introductionmentioning
confidence: 99%